Development of elephant apple fruit quality as affected by postharvest ethanol application and temperature - Sharif Hossain, A.B.M.; Nasrulhaq Boyce, A.; Mohamed, H. (2009)
Experiments were conducted to study the effects of temperature and ethanol application on the development and quality of the elephant apple fruit. Various treatments were carried out, viz., at room temperature (RT, 28°C), in exposed sunlight (ES,35°C), in 70 ethanol (ET, 28°C), under plastic covering (PC, 28°C), under plastic covering plus 70 ethanol (PCET, 28°C), at low temperatures (LT, 12°C) and at freezing temperature (FT, -1°C). The longest preservation time was observed in fruits preserved in FT (-1°C) and shortest in fruits preserved in ES (35°C) whilst the maturity index was highest in ES (35°C) treatments and lowest in FT (-1 °C) compared to the other treatments at the end of the experiments. However, fruits kept at FT (-1 °)exhibited chilling injury symptoms. Total Soluble Solids (TSS) was highest in ES (35°C) and PCET (28°) from the 1st to the 7th harvest compared to other treatments. A similar increasing trend in TSS was observed in all the treatments. On the contrary, Titratable Acidity (TA) was highest in FT (-1°C) and LT (12°C) from the 1st till the 7th harvest Similarly a declining trend of TA was found in all the other treatments. TSS was found to be higher in pulp than in peel in the ethanol treatment at 6, 12, 24, 48 and 72 h. However, TA was higher in peel than pulp. The results showed that low temperatures (LT and FT) and plastic covering with 70 ethanol (PCET) delayed ripening in elephant apple fruits and were the best preservation techniques. © 2009 Asian Network for Scientific Information.